2021
DOI: 10.18632/aging.203112
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9, both transcriptionally regulated by PU.1, promote epithelial-mesenchymal transformation (EMT) and invasive growth of dermal keratinocytes during scar formation post burn

Abstract: S100 calcium-binding protein A8 (S100A8) and S100A9 are small molecular weight calcium-binding regulatory proteins that have been involved in multiple chronic inflammatory diseases. However, the role of S100A8 and S100A9 in keratinocytes in wounded skin and how they are regulated during this process are still unclear. Here, we found that S100A8 and S100A9 were both upregulated in burn-wounded skins in vivo and thermalstimulated epidermal keratinocytes in vitro, accompanied by increased levels of epithelial-mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…4 E, Table s2). S100A9 has been proved to be transcriptionally regulated by PU.1 and AP-1, which was in concordance with our finding that the PU.1-related gene SPIB and AP-1 transcription factor FOSL1 were differentially expressed in S100A9-high group (Table s2) [ 44 , 45 ]. Notably, ESR1, the estrogen receptor coding gene, was among the overexpressed TFs in S100A9-low group, which further validated that estrogen receptor signaling could contribute to immune suppression [ 46 ].…”
Section: Resultssupporting
confidence: 91%
“…4 E, Table s2). S100A9 has been proved to be transcriptionally regulated by PU.1 and AP-1, which was in concordance with our finding that the PU.1-related gene SPIB and AP-1 transcription factor FOSL1 were differentially expressed in S100A9-high group (Table s2) [ 44 , 45 ]. Notably, ESR1, the estrogen receptor coding gene, was among the overexpressed TFs in S100A9-low group, which further validated that estrogen receptor signaling could contribute to immune suppression [ 46 ].…”
Section: Resultssupporting
confidence: 91%
“…3 G and H). The expressions of S100A8 and S100A9 associated with epithelial proliferation [ 30 ] were detected by qPCR. The results showed that the S100A8 and S100A9 expressions were significantly increased in IMQ group compared with the Control group (P < 0.001), while significantly decreased in the IMQ + Cap and IMQ + hDPSC groups (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…ZFP36 encodes tristetraprolin, an AU‐rich element RNA binding protein that is up‐regulated in wounded skin and controls inflammatory cytokines as well as neoplastic processes in keratinocytes (18,19). S100A2 regulates keratinocyte differentiation through its interaction with p53 (20), and expression of the alarmin S100A8 is associated with increased keratinocyte proliferation and epithelial–mesenchymal transition (21).…”
Section: Resultsmentioning
confidence: 99%
“…See Figure 1 for other definitions. keratinocyte proliferation and epithelial-mesenchymal transition (21).…”
Section: Cell-extrinsic Predictive Biomarkers Of Ssc Severitymentioning
confidence: 99%